2008
DOI: 10.1021/jo8014165
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Fluorescent Labeling Approaches for Naringenin, an Essential Flavonone in Plant Nitrogen-Fixation Signaling Pathways

Abstract: In search of an appropriate position for the fluorescent labeling, six chemically available positions of the flavonone core of naringenin have been examined. A number of azido-containing naringenin derivatives were accordingly prepared in various site-specific fashions, and the mild Cu(I)-catalyzed Huisgen 1,3-dipolar cycloaddition successfully served as the common "Click" labeling tool in the final steps. On the basis of the biological activities of the first batch of labeled compounds, further optimization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Fluorescence labeling was used to detect the bindings of naringenin to nod-D after its entry into Rhizobium cells. In the corresponding fluorescence imaging experiments, it was observed that the entry of naringin into living Rhizobium cells was clear [10]. Methods with fluorescent labels have the potential to achieve the low limits of detection (LOD) imposed by legislation when interferences resulting from the sample matrix are reduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence labeling was used to detect the bindings of naringenin to nod-D after its entry into Rhizobium cells. In the corresponding fluorescence imaging experiments, it was observed that the entry of naringin into living Rhizobium cells was clear [10]. Methods with fluorescent labels have the potential to achieve the low limits of detection (LOD) imposed by legislation when interferences resulting from the sample matrix are reduced.…”
Section: Introductionmentioning
confidence: 99%
“…It can visually display the conduction of drugs in plants. In view of these considerations, this experiment took tobacco plants as the experimental object, using UPLC-HRMS [30] and fluorescent dual-light sub-confocal real-time imaging technology [10,31,32] to carry out the systemic conduction study of vanisulfane in the plant.…”
Section: Introductionmentioning
confidence: 99%
“…The long-standing model on nod gene induction sees the rhizobial NodD transcriptional activator protein as a flavonoid-perceiving unit that is localized at the cytoplasmic bacterial membrane where it is postulated to bind with the incoming plant flavonoids. While the binding of NodD to the nod box promoter of the common nod genes is an ascertained event, the binding of NodD to flavonoids has not yet been demonstrated in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Reported protocols for the fluorescent labeling of natural products involving several reaction steps along with purification and protection–deprotection procedures are tedious and result in low overall yield. , Indeed, the availability of natural products is scanty in most of the cases due to their low abundance in natural sources, making it difficult to carry out all the required steps. Second, widely used tags (such as fluorescein, rhodamine) are bulkier in nature, which may lead to loss of biological activity. , Although ready to use fluorescent tags are available commercially, they are quite expensive and require extreme reaction conditions for labeling (e.g., NBD-F or DBD-COCl needs 60 °C at basic pH), which restrict their use for tagging sensitive multifunctional natural products. Consequently, there is a need for the development of an inexpensive, mild, and high-yielding protocol for the fluorescent labeling of biologically active complex natural products capable of maintaining the activity in a labeled derivative. In this article we have demonstrated a one-pot labeling protocol for hydroxylated bioactive compounds by a 7-nitrobenzo-2-oxa-1,3-diazole (NBD)-based tag which was successfully applied to label several complex multifunctional molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Reported protocols for the fluorescent labeling of natural products involving several reaction steps along with purification and protection−deprotection procedures are tedious and result in low overall yield. 12,13 Indeed, the availability of natural products is scanty in most of the cases due to their low abundance in natural sources, making it difficult to carry out all the required steps. Second, widely used tags (such as fluorescein, rhodamine) are bulkier in nature, which may lead to loss of biological activity.…”
Section: ■ Introductionmentioning
confidence: 99%